Cumulative Intracranial Tumor Volume (CITV) Enhances the Prognostic Value of the Lung-Specific Graded Prognostic Assessment (GPA) Model. Issue 2 (August 2016) - Marcus, Logan P.; Marshall, Deborah; Hirshman, Brian R.; McCutcheon, Brandon A.; Gonda, David D.; Koiso, Takao; Hattangadi-Gluth, Jona A.; Carter, Bob S.; Yamamoto, Masaaki; Chen, Clark C.
Abstract : BACKGROUND: Management of patients afflicted with brain metastasis requires tailoring of therapeutic strategies based on survival expectations. Therefore, the development of prognostic indices is of critical importance in this patient population. OBJECTIVE: To determine whether the cumulative intracranial tumor volume (CITV) of brain metastasis augments the prognostic value of the lung-specific Graded Prognostic Assessment (GPA) index. METHODS: Patient data were derived from 365 lung cancer patients with brain metastasis who were consecutively treated with stereotactic radiosurgery at the University of California, San Diego/San Diego Gamma Knife Center. CITV was analyzed to determine the volume cutoff that maximized sensitivity and specificity for 1-year survival. Multivariate Cox proportional hazard modeling was performed, and overall survival was estimated by the Kaplan-Meier method risk stratifying with or without this optimal CITV. The prognostic value of these models (lung-specific GPA ± CITV) was quantitatively compared with the use of net reclassification improvement (>0) and integrated discrimination improvement. RESULTS: For the University of California, San Diego/San Diego Gamma Knife Center cohort, the CITV cutoff that had the greatest survival discrimination at 1 year was 4 cm 3 . The addition of CITV to the lung-specific GPA indexes significantly improved the prognostic value of lung-specific GPA, with net reclassification improvement >0 of 0.430 (95% confidence interval, 0.228-0.629) and integrated discrimination improvement of 0.029 (95% confidence interval, 0.004-0.073). These findings were validated in an independent cohort of 1638 lung cancer patients with brain metastasis who were treated with stereotactic radiosurgery at the Katsuta Hospital Mito Gamma House in Japan. CONCLUSION: In independent cohorts, the addition of CITV to the lung-specific GPA index significantly improved the prognostic value of this index. ABBREVIATIONS: AUC, area under the receiver-operating characteristic curve BM, brain metastasis CITV, cumulative intracranial tumor volume ds-GPA, disease-specific Graded Prognostic Assessment GPA, Graded Prognostic Assessment IDI, integrated discrimination improvement KHMGH, Katsuta Hospital Mito Gamma House KPS, Karnofsky Performance Status NRI, net reclassification improvement ROC, receiver-operating characteristic curve SRS, stereotactic radiosurgery UCSD/SDGKC, University of California, San Diego/San Diego Gamma Knife Center Abstract : Supplemental Digital Content is Available in the Text.